Advances in Water Resource Monitoring and Modelling: Water Quantity and Quality Issues - Copetti, Diego (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The availability of fresh water of good or high quality is essential for the health of people, animals and the environment. The monitoring and modelling of water resources are therefore strategic for achieving a sustainable and inclusive society. This reprint hosts research and review papers featuring different approaches ranging from engineering and environmental sciences (hydrology, ecotoxicology and remote sensing) to economic disciplines (environmental and circular economy). Contributions may be of interest to both researchers and environmental managers.